Theorizing on social enterprise behaviors in challenging environments – evidence from five social cooperatives in Poland - Marzena Starnawska (Gdańsk University of Technology, Faculty of Management and Economics, 2015)
Entrepreneurial behavior in challenging institutional environments have been widely investigated in the literature. One of the characteristics of these environments is resource scarcity. This is particularly valid in the context of social entrepreneurship and social enterprises. The aim of this paper is to identify entrepreneurial behaviors in social entrepreneurship and what is happening behind these processes in the context of transition country, against the backdrop of challenging environment and weak institutional framework in particular in Poland. We use a purposive sample of 5 social cooperatives, and report the data from several in-depth interviews with their representatives as well as observation from the cooperatives. We have attempted to widen the existing categories on entrepreneurial behavior namely boundary blurring and diversification, and discuss them in social entrepreneurship context.
Keywords: L31; L26; P13; D22; D02; 330; social entrepreneurship; social enterprise; entrepreneurial behavior; social cooperatives; institutions